Euro Area Policies : Spillover Report for the 2011 Article IV Consultation and Selected Issues. (IMF Staff Country Reports; Country Report, 2011)
The euro area (EA) plays a major role in the global economy. Market perceptions of events in the EA program countries illustrate the possibility of large spillovers from the area in times of stress. The prospect of large spillovers underscores the urgent need for actions to contain, and eventually overcome, the ongoing crisis. The planned fiscal consolidation in the EA could benefit the rest of the world. Spillovers from gradual monetary policy normalization appear manageable. Execution of the structural reform agenda will carry positive spillovers.